(3GdChGFds - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO GHf jMji Hf egQGf GdnYrSncQj, CHh gdGd,J (B395 (3g` s ((3TQa GdOjf GdMSjf Hf CejQ GdeDefjf GdbGSe Hf eMeO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY QJHI GdCOH hPhjg hbGd BNQ (B: (3YQVJ hLgi hOfG EfWdGbi hGdeGA jafi hGdKfGA HGbi hNjQ GdYde eG jfaY , hCfaYg eG jMGVQ Hg s
(3BNQgG (B:s
(3jJab BNQgG eY BNQ GdfSNI GdChdi , HENJdGai ai HYV GdCdaGX hGdYHGQGJ s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3cJHJ Hbde eVHhWs
(3HChdgG Jedc ddfGSN s
(3hai BNQgG Jedc dCHfg ef HYOg CMeO s
(3HBNQgG ebGHdI JeJ Ydi GdCe GdefShN efgG ai BNQ TYHGf SfI (B1035(3g` s
Keywords: (3GdJGQjNs